MULTILETRAMENTOS E TECNOLOGIAS NO ENSINO DE LÍNGUA INGLESA NA ESCOLA PÚBLICA - Santos, Cristiane Martins dos (2023)
In this thesis, inserted in the research line Teaching and Teaching Practices, of the Master‟s Degree in the Teaching Humanities and Languages from the Franciscan University, we seek to evaluate how practices of multiliteracy and technological resources are used by English language teachers in the municipal school of Santa Maria, RS. As specific objectives, we tried to contextualize the perspective of literacy and the use of technology in English language teaching; to check which technological resources are used by English Language teachers in the selected schools; to map the characteristics related to the use of technology in the English language teaching at these schools; to understand how digital literacy practices are carried out in the English Language teaching and if they are reality in the evaluated schools; The qualitative research, from exploratory and descriptive approach, is characterized as a case study developed in two schools of Santa Maria, RS, with two participants, English language teachers. Data were collected through classroom observation, analysis of teaching materials and interviews. In the schools where the study was carried out it was noticed that there is a certain difficulty in combining theory and practice in the classroom, probably due to the lack of time to prepare didactic material, the unavailability of technological resources and the context of students. It was also possible to identify that, although the technologies are prominent in language teaching, and teachers recognize the importance of using these resources for the teaching and learning of the English Language, their use in pedagogical practices is rather limited. The study shows that teachers are developing multiliteracy activities in the classroom, but they are not linked to digital technologies, but to printed materials and didactic materials. Thus, it was found that there is still much to be done in order to use technological resources to promote digital literacy in schools.